Pengaruh Asuransi Kesehatan dan Empati terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit: Meta-Analisis - Ismail, Aem; Maghfiroh, Halimah Aulia Ita (LPPM Institut Pendidikan Nusantara Global, 2025)
Hospitals are health service institutions that have a central role in providing medical services to the community. The quality of service provided by hospitals greatly determines the level of patient satisfaction. Patient satisfaction is not only influenced by the results of treatment, but also by various other aspects such as the friendliness of medical personnel, speed of service, comfort of facilities, a sense of empathy by medical personnel, the use of health insurance and ease of administration. The purpose of this study is to find out how much health insurance and empathy affect outpatient satisfaction in hospitals. This study is a meta-analysis research with article search conducted based on the feasibility criteria of the PICO model, including: P = Outpatient; I= Health and empathy insurance; C= No health insurance and no empathy; O= Patient satisfaction. Articles were collected from Google Scholar, PubMed and Science Direct. Keywords use